Determinant of Regional Economic Growth in East Java, Indonesia - Muchlas Manduli Sengaji; Sasongko Sasongko; Rachmat K Sakti (Universitas Negeri Malang, 2019)
National economic growth is an aggregation of regional economic growth. Growth is also the main measure of development success. The existence of fiscal decentralization provides flexibility to local governments in regulating their regions and making policies that can support the potentials in their regions. This study aims to analyze and provide empirical evidence about the determinants of economic growth in 38 regencies/cities in East Java Province in 2010 to 2016 including Locally-generated Revenues (PAD), General Allocation Funds (DAU), Special Allocation Funds (DAK), Revenue Sharing Funds (DBH), Indirect Expenditures, Direct Expenditure, and Remaining Over Budget Financing (SiLPA). From the results of the Fixed Effect model, it was found that the PAD, DAU, DBH and Direct Expenditure had a positive significant effect on economic growth, while the DAK and Indirect Spending variable had no significant effect on economic growth. SiLPA also had no significant effect on economic growth. The last, simultaneously, PAD, DAU, DAK, DBH, Direct Expenditure, Indirect Expenditure and SiLPA had a significant effect on economic growth.